Description of new taxa, both in Scelioninae and Telenominae (Hymenoptera Scelionidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
From material collected in Sicily, numerous taxa of Scelionid wasps have so far been identified by the author, viz.: Cremastobaeus sp., Palpoteleia nr. atra Kieffer, Paridris sp., Anteromorpha sp., Calliscelio sp., Probaryconus cristatus n. sp., Thoran metallicus Curtis. The first three above-mentioned genera are new to Italian entomofauna, while the others are recorded in Sicily for the first time. Robertella dessarti n. gen. et n. sp., belonging to Telenominae, was bred from a Nysius sp. infesting the flowers of Pulicaria dysenterica (L.).
Keywords: Scelioninae; Probaryconus cristatus n. sp.; Telenominae; Robertella n. gen.; dessarti n. sp .